Cancerous ovarian stem cells: Obscure targets for therapy but relevant to chemoresistance1. Issue 1 (14th November 2012) - Ahmed, Nuzhat; Abubaker, Khalid; Findlay, Jock; Quinn, Michael
Abstract Chemotherapy with platinum and taxanes is the first line of treatment for all epithelial ovarian cancer (EOC) patients after debulking surgery. Even though the treatment is initially effective in 80% of patients, recurrent cancer is inevitable in the vast majority of cases. Emerging evidence suggests that some tumor cells can survive chemotherapy by activating the self‐renewal pathways resulting in tumor progression and clinical recurrence. These defined population of cells commonly termed as "cancer stem cells" (CSC) may generate the bulk of the tumor by using differentiating pathways. These cells have been shown to be resistant to chemotherapy and, to have enhanced tumor initiating abilities, suggesting CSCs as potential targets for treatment. Recent studies have introduced a new paradigm in ovarian carcinogenesis which proposes in situ carcinoma at the fimbrial end of the fallopian tube to generate high‐grade serous ovarian carcinomas, in contrast to ovarian cortical inclusion cysts (CIC) which produce borderline and low grade serous, mucinous, endometrioid, and clear cell carcinomas. This review summarizes recent advances in our understanding of the cellular origin of EOC and the molecular mechanisms defining the basis of CSC in EOC progression and chemoresistance. Using a model ovarian cancer cell line, we highlight the role of CSC in response to chemotherapy, and relate how CSCs may impact on chemoresistance and ultimately recurrence. We also propose the molecular targeting of CSCs and suggest ways that may improve the efficacy of current chemotherapeutic regimens needed for the management of this disease. J. Cell. Biochem. 114: 21–34, 2012. © 2012 Wiley Periodicals, Inc.